Bipolar Fuzzy Filters in BL-Algebras - Alqahtany, Manal Abdullah; Dale, Tanisha Bhagwan (IndoMS, 2025)
This research introduces and examines the novel concept of filters in BL-algebras constructed upon bipolar fuzzy structures. Specifically, we present the formulation of bipolar fuzzy filters (BFFs) within the context of BL-algebras and conduct a comprehensive investigation of their associated properties. This work extends the traditional notion of filters in BL-algebras by incorporating the bipolarity aspect of fuzzy logic, thereby providing a more nuanced framework for analyzing logical structures. Our study not only establishes the fundamental definitions but also explores the theoretical implications and characteristics of these bipolar fuzzy filters, contributing to the broader understanding of many-valued logic systems and their algebraic representations.